Al-Taṣawwuf wa Madlūluh ʻInd al-Bāḥithīn fī al-Tārīkh al-Taṣawwuf - Irfan Mas'ud (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2007)
The issue of the tasawuf meaning from semantic aspects is a study that was much done by the observer of tasawuf or Islamic mysticism. This paper explores and presents some viewpoints the observer of tasawuf and tasawuf people that is considered authoritative regarding tasawuf linguistic understanding.